The scopes of rational using of road and rail transport while delivering lime bricks in Ukraine - Olkhova, Maria (Lviv Polytechnic Publishing House, 2015)
The challenge of transport mode choice is one of core logistics tasks. The plenty of solutions of this task is based on the main features of transport and can not be used for specific situations effectively. Researching of delivery variants of lime bricks is actual seeing rapid development and possibility of using diverse transport packaging. Equivalent distance calculation allows to determine the scope of using rail and road transport. In contrast to the existing approaches of calculating of equivalent distance, this paper is proposed to use customer’s cost as criterion of transport mode choice, including immobilisation cost while transporting goods.
Keywords: customer’s cost; road; rail; equivalent distance